Trends in shore-based angling effort determined from aerial surveys: a case study from KwaZulu-Natal, South Africa. Issue 3 (1st October 2020) - Mann, BQ; Mann-Lang, JB
Abstract : Understanding the spatiotemporal characteristics of effort is a critical component of managing fisheries. Recreational shore-angling is the largest sector of the linefishery and one of the primary recreational activities undertaken along the coast of KwaZulu-Natal (KZN), South Africa. The aim of this study was to make a reliable estimate of current total shore-based angling effort in KZN and to examine the spatial and temporal distribution of the effort. To do this, randomised monthly flights to count shore-anglers in an 'instantaneous' manner were conducted along the entire KZN coastline between January and December 2018, and then compared with similar aerial surveys conducted in 1994/95 and 2007/08. A total of 44 flights were undertaken, with 21 and 23 flights conducted along the north and south coasts, respectively. Ground-truthing revealed that the aerial counts of shore-anglers were 89% accurate. Angler effort was significantly higher over weekends and during good-weather days. Seasonality of shore-based angling effort showed that greatest effort occurred during the winter months (June to September), coinciding with the seasonal availability of popular angling species. More-developed stretches of the KZN coast with higher population densities and easier beach-access had the highest angling effort. Total annual angler effort was calculated to be 785 538 angler-days y–1, which represents a 22.9% decline from the estimate made in 1994/95 and a 6.9% decline from the estimate made in 2007/08. Spatial distribution of shore-based fishing effort was very similar in 2007/08 and 2018, with the major differences being a decrease in fishing effort at St Lucia and Maphelane, and a slight increase in effort on the 'upper' (northern) south coast during 2018. Based on the results of this study, recommendations for improved management of the KZN shore fishery include: (i) follow-up using an independent roving-creel survey; (ii) improvement of coastal law enforcement; (iii) implementation of a linefish observer programme; and (iv) a repeat of the aerial survey every 10 years.